Income Distribution and Demand-Induced Innovations - Foellmi, Reto; Zweimüller, Josef (Review of Economic Studies, 2006)
We introduce non-homothetic preferences into an innovation-based growth model and study how income and wealth inequality affect economic growth. We identify a (positive) price effect—where increasing inequality allows innovators to charge higher prices and (negative) market-size effects—with higher inequality implying smaller markets for new goods and/or a slower transition of new goods into mass markets. It turns out that price effects dominate market-size effects. We also show that a redistribution from the poor to the rich may be Pareto improving for low levels of inequality.